Development And Utilization Of Aerobic Granular Biomass In Palm Oil Mill Effluent (Pome) Treatment - Kanadasan, Gobi (2011)
Palm oil mill effluent (POME) discharged without proper treatment could cause severe environmental problem in Malaysia. The conventional biological treatment method using activated sludge in series of ponds is considered obsolete. Hence, in this work, aerobic granular biomass was developed and utilized for the treatment of POME in the sequencing batch reactor (SBR). The mean diameter of the developed aerobic granule was 0.9 mm. The developed aerobic granule managed to remove about 88% of the influent COD at average, throughout the operation of SBR.